The WASCAL Hydrometeorological Observatory in the Sudan Savanna of Burkina Faso and Ghana. Issue 1 (13th December 2018) - Bliefernicht, J.; Berger, S.; Salack, S.; Guug, S.; Hingerl, L.; Heinzeller, D.; Mauder, M.; Steinbrecher, R.; Steup, G.; Bossa, A.Y.; Waongo, M.; Quansah, E.; et al.
Abstract : Core Ideas: A new hydrometeorological observatory was established for the Sudan Savanna. More than 30 hydrometeorological variables in subhourly resolution are provided. Water, energy, and CO2 fluxes are monitored along a land use change gradient. The data form the basis for an improved impact assessment of environmental changes. It is an excellent platform for future field and modeling studies in West Africa. Watersheds with rich hydrometeorological equipment are still very limited in West Africa but are essential for an improved analysis of environmental changes and their impacts in this region. This study gives an overview of a novel hydrometeorological observatory that was established for two mesoscale watersheds in the Sudan Savanna of Southern Burkina Faso and Northern Ghana as part of the West African Science Service Centre on Climate Change and Adapted Land Use (WASCAL) program. The study area is characterized by severe land cover changes due to a strongly increasing demand of agricultural land. The observatory is designed for long‐term measurements of >30 hydrometeorological variables in subhourly resolution and further variables such as CO2 . This information is complemented by long‐term daily measurements from national meteorological and hydrological networks, among several other datasets recently established for this region. A unique component of the observatory is a micrometeorological field experiment using eddy covariance stations implemented at three contrasting sites (near‐natural, cropland, and degraded grassland) to assess the impact of land cover changes on water, energy, and CO2 fluxes. The datasets of the observatory are needed by many modeling and field studies conducted in this region and are made available via the WASCAL database. Moreover, the observatory forms an excellent platform for future investigations and can be used as observational foundation for environmental observatories for an improved assessment of environmental changes and their socioeconomic impacts for the savanna regions of West Africa.